EVALUASI KESESUAIAN LAHAN TANAMAN TOMAT DI NAGARI AIA DINGIN KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK (Jurnal Pelangi : Research of Education and Development, 2011)
This study aims to evaluate land suitability of tomato plants and createmaps of land suitability of tomato plants in the Valley of the Nagari Aia ColdGumanti Solok District. Soil at the sites is soil that develops Andisol of volcanicrocks. The unit of analysis in this study is the suitability of tomato crop land inNagari Aia Cold Valley Gumanti Solok District. Corresponding map of thelocation of the study Nagari cold Aia Valley Gumanti Solok District 1: 50,000scale in order to get the five points that the samples Jorong Data, Jorong Koto,Jorong Aia Sonsang (dryland) and Jorong Aia Sonsang and Jorong Data (wetland/ paddy). The data analysis conducted in the field and in the laboratory by meansof "matching" between the quality or characteristics of the land on condition ofgrowing tomato plants. To calculate the indices of climate and land use methodsStorie and Square Root. Land suitability assessment in the five study sitesrepresenting the Valley of the Nagari Aia Cold Gumanti Solok district to JorongData and Jorong Koto land suitability classes N1, there is a severe limiting factorin the availability of water is rainfall and potential of mechanization the slopes aswell as nutrient retention is pH, but This can be enhanced S3 (marginally suitable)for tomato plants is by liming and terracing, guludan / beds and mulching. In thearea of fitness classes land Jorong Aia Sonsang the N2, the limiting factor on theslopes there are very heavy so it can not be repaired. Jorong Aia Sonsang andJorong Data, (wetland / paddy) land suitability class S3m classified, there aresevere limiting factor in the availability of water is rainfall, but this can beupgraded to S2 (moderately suitable) for tomato plants, by taking into account thecondition of the lowest rainfall based on agricultural climate zones.